Engineering the variable region of therapeutic IgG antibodies - Igawa, Tomoyuki (Landes Bioscience, 2011)
Since the first generation of humanized IgG1 antibodies reached the market in the late 1990s, IgG antibody molecules have been extensively engineered. The success of antibody therapeutics has introduced severe competition in developing novel therapeutic monoclonal antibodies, especially for promising or clinically validated targets. Such competition has led researchers to generate so-called second or third generation antibodies with clinical differentiation utilizing various engineering and optimization technologies. Parent IgG antibodies can be engineered to have improved antigen binding properties, effector functions, pharmacokinetics, pharmaceutical properties and safety issues. Although the primary role of the antibody variable region is to bind to the antigen, it is also the main source of antibody diversity and its sequence affects various properties important for developing antibody therapeutics. Here we review recent research activity in variable region engineering to generate superior antibody therapeutics.